Case Report: Kyrieleis plaques in an unusual Behcet's disease uveitis - Li, Jiani; Zhao, Tantai; Guo, Xiaojian; Xiao, Yangyan (Frontiers in Medicine, 2025)
Kyrieleis plaques are a rare retinal manifestation that has rarely been reported in Behcet's disease uveitis. We report the case of a 41-year-old man who presented with Behçet's disease uveitis combined with central serous chorioretinopathy. Laboratory studies showed positive for human leukocyte antigen B51. Polymerase chain reaction analysis of aqueous humor excluded infectious uveitis. Kyrieleis plaques were observed in the bilateral retinal arteries. These plaques persisted in both eyes after half a year of immunosuppressive treatments. Kyrieleis plaques are not limited to infectious uveitis; they can also be associated with Behçet's disease uveitis.